Studi Analisis Penerapan Metode Arc-Length Dalam Mendeteksi Retak Awal Beton Bertulang - Rafifah, Dwi; Clara, Amanda (Dept. of Civil Engineering Universitas Riau, 2025)
The implementation of the arc-length method to enhance early-crack sensitivity in finite element models of reinforced concrete. Indonesia’s seismic vulnerability raises the importance of early crack detection for structural safety, particularly as cracks in reinforced concrete beams critically affect performance and integrity. The review compares three numerical modelling approaches—embedded reinforcement, Material Point Method (MPM), and Cracking Element Method (CEM) and analyzes their limitations in accurately capturing the onset of cracking. The embedded method often lacks sensitivity for early crack detection due to solver convergence challenges, MPM struggles with local stress concentration accuracy, and CEM depends heavily on precise crack initiation criteria. Integrating the arc-length method with these approaches significantly improves model stability and crack initiation sensitivity by enabling robust solution tracking through nonlinear and critical response phases. Case studies and referenced research demonstrate that arc-length-augmented approaches yield more reliable simulations, closely aligning with experimental results. This review concludes that the arc-length method provides a key numerical advance for early crack analysis in reinforced concrete, supporting safer earthquake-resistant design and maintenance strategies.